Access to information on the requirements to work as a nurse in Poland, provided to Ukrainian refugee background nurses by nursing self-government institutions. Word Wide Web Content Analysis - Cieślak, Ilona; Panczyk, Mariusz; Jaworski, Mariusz; Theofanidis, Dimitrios; Gotlib, Joanna (Nursing in the 21st Century, 2023)
ACCESS TO INFORMATION ON THE REQUIREMENTS TO WORK AS A NURSE IN POLAND, PROVIDED TO UKRAINIAN REFUGEE BACKGROUND NURSES BY NURSING SELF-GOVERNMENT INSTITUTIONS. WORD WIDE WEB CONTENT ANALYSISAim. The aim of the study was to determine whether the National Chamber of Nurses and Midwives (NIPiP), as well as the District Chambers of Nurses and Midwives (OIPiP), undertake activities to inform Ukrainian war refugees - nurses (UKR-Ns) about the simplified work permit procedure.Material and methods. We analysed work permit related information for UKR-Ns available on the NIPIP and OIPIP websites. The research was conducted in two stages: 1) content analysis of information for UKR-Ns posted on the official NIPiP website 2) quantitative and qualitative analysis of information for UKR-Ns on official OIPIP websites.Results. The analysis of information on work permits demonstrated that its content and the way in which this information was communicated varied greatly over time. Seven OIPIs did not publish any information on the procedure of obtaining work permits by UKR-Ns and for three OIPIPs, access to information was modified and/or removed from the website at the time of the observation undertaken. The vast majority of OIPIPs provided information that could only be considered as partly relevant.Conclusions. The information for UKR-Ns, regarding the process of obtaining work permits, published by the NIPiP and OIPiPs on their official websites requires modification, both in terms of content and form.